Development and Urgency of Administrative Law Tools After the Enactment of Law No. 2 April 2020 During the COVID-19 Pandemic - Sitti Harlinah; Andi Sri Rezky Wulandari (Yayasan Adra Karima Hubbi, 2024)
Background. The spread of the new coronavirus has affected the world, including Indonesia, for more than a year. Purpose. The purpose is to determine the position of administrative legal instruments in the formation of public policy, as well as analyze developments and the urgency of administrative law as an alternative to government policy during the Covid-19 pandemic. Method. The type of survey used in this survey is Prescriptive Legal namely with legal approach. The nature of the research used in this writing is descriptive analytical, which is qualitatively analyzed to answer the legal issues be faced. Legal materials used are primary, secondary, tertiary legal materials. The research method used in this research is the normative legal method. Results. The results of this study are expected to be a reference for future analytical research and legal design, especially legal design related to the application of administrative law. The research method used in this research is the normative legal method. The type of research used in this text is descriptive and analytical. Conclusion. Conclusion is the instruments of administrative law in the formation of public policy develop dynamically over time along with the needs of the state and citizens.